Stem cell-like breast cancer cells with acquired resistance to metformin are sensitive to inhibitors of NADH-dependent CtBP dimerization. (22nd January 2019) - Banerjee, Arindam; Birts, Charles N; Darley, Matthew; Parker, Rachel; Mirnezami, Alex H; West, Jonathan; Cutress, Ramsey I; Beers, Stephen A; Rose-Zerilli, Matthew J J; Blaydes, Jeremy P
Abstract: Altered flux through major metabolic pathways is a hallmark of cancer cells and provides opportunities for therapy. Stem cell-like cancer (SCLC) cells can cause metastasis and therapy resistance. They possess metabolic plasticity, theoretically enabling resistance to therapies targeting a specific metabolic state. The C-terminal binding protein (CtBP) transcriptional regulators are potential therapeutic targets in highly glycolytic cancer cells, as they are activated by the glycolytic coenzyme nicotinamide adenine dinucleotide (NADH). However, SCLC cells commonly exist in an oxidative state with low rates of glycolysis. Metformin inhibits complex I of the mitochondrial electron transport chain; it can kill oxidative SCLC cells and has anti-cancer activity in patients. SCLC cells can acquire resistance to metformin through increased glycolysis. Given the potential for long-term metformin therapy, we have studied acquired metformin resistance in cells from the claudin-low subtype of breast cancer. Cells cultured for 8 weeks in sub-IC50 metformin concentration proliferated comparably to untreated cells and exhibited higher rates of glucose uptake. SCLC cells were enriched in metformin-adapted cultures. These SCLC cells acquired sensitivity to multiple methods of inhibition of CtBP function, including a cyclic peptide inhibitor of NADH-induced CtBP dimerization. Single-cell mRNA sequencing identified a reprogramming of epithelial–mesenchymal and stem cell gene expression in the metformin-adapted SCLC cells. These SCLC cells demonstrated an acquired dependency on one of these genes, Tenascin C. Thus, in addition to acquisition of sensitivity to glycolysis-targeting therapeutic strategies, the reprograming of gene expression in the metformin-adapted SCLC cells renders them sensitive to potential therapeutic approaches not directly linked to cell metabolism. Abstract : Acquired resistance to metformin was used to investigate the role of oxidative phosphorylation in determining the phenotype, and therapeutic vulnerabilities, of triple-negative breast cancer stem cell-like cells.